Pembinaan Calon Pasangan Katolik Melalui Kursus Persiapan Perkawinan. Penguatan Pemahaman Tentang Hakikat, Tujuan, dan Sifat Sakramental Perkawinan Katolik - Lelu, Skolastika (Abdimas Mandalika, 2026)
Abstract: This community service activity was conducted at St. Ignatius Waibalun Parish by lecturers of STP Reinha Larantuka in collaboration with the parish pastoral team. The activity was motivated by the low level of theological understanding among Catholic couples regarding the sacrament of marriage, which is often perceived merely as an emotional and social union. The purpose of this activity was to prepare prospective Catholic couples to understand the meaning, purpose, and essential nature of Catholic marriage, as well as the responsibilities of faith in family life. The implementation method was carried out through a Marriage Preparation program consisting of three main stages: introduction to Church teachings on marriage, faith reflection, and practical accompaniment. A total of 15 engaged couples actively participated in the program through interactive lectures, group discussions, couple communication simulations, and personal reflection. Evaluation was conducted descriptively through observation and interviews to assess improvements in participants’ understanding and spiritual readiness. The results showed an increase in theological and spiritual understanding by 41.7%, greater awareness of sacramental fidelity, and 85% spiritual readiness to receive the sacrament of marriage. This program had a positive impact on the spiritual and psychological readiness of participants, while strengthening their commitment to living family life according to Church teachings. The activity is expected to serve as a sustainable model for family pastoral ministry in the parish.Abstrak: Kegiatan pengabdian kepada masyarakat ini dilaksanakan di Paroki St. Ignasius Waibalun oleh dosen STP Reinha Larantuka bersama tim pastoral paroki. Kegiatan ini dilatarbelakangi oleh rendahnya pemahaman teologis calon pasangan Katolik tentang sakramen perkawinan yang masih dipandang sebatas ikatan emosional dan sosial. Tujuan kegiatan ini adalah mempersiapkan calon pasangan agar memahami makna, tujuan, dan sifat dasar perkawinan Katolik serta tanggung jawab iman dalam kehidupan keluarga. Metode pelaksanaan dilakukan melalui pembinaan Persiapan Perkawinan yang terdiri atas tiga tahap utama, yaitu pengenalan ajaran Gereja tentang perkawinan, refleksi iman, dan pendampingan praktis. Sebanyak 15 pasangan calon suami istri mengikuti kegiatan secara aktif melalui ceramah interaktif, diskusi kelompok, simulasi komunikasi pasangan, dan refleksi pribadi. Evaluasi dilaksanakan secara deskriptif melalui observasi dan wawancara untuk menilai peningkatan pemahaman, dan kesiapan rohani peserta. Hasil kegiatan menunjukkan peningkatan pemahaman teologis dan spiritual sebesar 41,7%, kesadaran akan kesetiaan sakramental, serta kesiapan rohani 85% dalam menerima sakramen perkawinan. Program ini berdampak positif terhadap kesiapan rohani dan psikologis peserta dalam menerima sakramen perkawinan, sekaligus memperkuat komitmen mereka untuk hidup berkeluarga sesuai ajaran Gereja. Kegiatan ini diharapkan menjadi model pembinaan berkelanjutan bagi pelayanan pastoral keluarga di paroki